ANALISIS PENGARUH OPINI, TEMUAN DAN KARAKTERISTIK DAERAH TERHADAP KINERJA KEUANGAN PROVINSI JAMBI - Muhammad Rafi Bakri (JURNAL AKUNTANSI, 2022)
Financial performance is an indicator in determining the performance of local governments in managing regional finances. This study aims to empirically measure the effect of audit opinions and audit findings by BPK RI and regional characteristics on the financial performance of Jambi Province. Regional characteristics that become variables in this study are the level of independence and dependence on the central government. Financial performance can be measured using the ratio of effectiveness and efficiency. The population in this study was 9 districts and 2 cities in Jambi Province in 2017-2019. The analytical method used is quantitative analysis with multiple linear regression models. The results showed that the level of independence, the level of dependence on the central government, and the findings of each examination partially affected the level of effectiveness and efficiency of district/city financial management in Jambi Province. However, the audit opinion has no significant effect on the financial performance. Furthermore, the opinions, findings of the examination and regional characteristics simultaneously have a substantial impact on the financial performance of districts/cities in Jambi Province in 2017-2019.